HUBUNGAN PERSONAL HYGIENE DAN KONDISI LINGKUNGAN DENGAN KEJADIAN PENYAKIT SKABIES DI PANTI ASUHAN DHUAFA - Silvia Indah Desvita S.; Tri Lestari (Rena Cipta Mandiri, 2025)
The World Health Organization (WHO) in 2022 stated that the prevalence of scabies cases was 130 million people in the world. The definition of Hygiene is an effort by humans to make themselves healthy with steps such as caring for and maintaining personal hygiene such as washing hands with clean water and soap so that hands are clean, throwing away rotten/unfit for eating sides which have an impact on maintaining the nutritional content of food as a whole. The purpose of this study is to determine personal hygiene and environmental conditions with the incidence of scabies. The results of the study showed a significant relationship between personal hygiene and environmental conditions with the incidence of scabies in Orphanages for the Poor.